Modern Society and Its Value Orientations. - Yaralyan, Karine (Bulletin of Yerevan University E: Philosophy, Psychology, 2018)
The current pace of social and technological changes mainstreams the issue of social and psychological adaptation into society. A human being is propelled into a decentralized and constantly spinning around the world with its dynamics being dangerous, on the one hand, but still attractive, on the other hand. At the same time, it becomes increasingly obvious that, in this world, “taking one’s chance” isn’t possible unless everyone is extremely flexible and mobile, as well as capable to act as an independent social unit. All this has inevitably affected the value system of the modern man that, on the one hand, is guided by his own self-presentableness and stance of distance pointing towards the values of the creativeness-, knowledge- and innovation-associated self-expression, while on the other hand, within the context of co-implication and solicitude, is reinforced in the system of enlightened self-interest (or rational selfishness) with certain sublation of the connection between existence and oughtness.
Keywords: risk society, individualization, interpersonal loneliness, anthropologic shock, existential crisis, distancing, self-expression values, rational selfishness